A literature review on the usage of Technology Acceptance Model for analysing a virtual reality's cycling sport applications with enhanced realism fidelity - Mahalil I.; Yusof A.M.; Ibrahim N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Virtual reality; Wind effects; Basic elements; Interactive platform; Literature reviews; Technology acceptance model; Temperature level; The unified theory of acceptance and use of technology(UTAUT); Training exercise; Users' acceptance; Sports